SINERGITAS PENGAWASAN INSTANSI PUSAT DAN DAERAH TERHADAP LARANGAN IMPOR PAKAIAN BEKAS DI KABUPATEN INDRAGIRI HILIR TAHUN 2016-2017 - Andira, Ayu; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Used clothing is clothing that is bought and used from the first consumer and then resold to the second consumer or so on. These clothes have a special attraction for the community, in addition to having good quality as well as relatively cheap prices, generally these used clothes have brands that have been recognized for their quality and with models that are not outdated. If we look at the history, the Tembilahan community has started trading used clothing around the 1980s.This study aims to describe the Synergy of Supervision of Central and Regional Agencies in Prohibiting the Import of Used Clothing in Indragiri Hilir Regency 2016-2017. The location of this study was conducted in Tembilahan City, Indragiri Hilir Regency. Data collection techniques are carried out by observation, interviews and documentation. The method used in this study is qualitative descriptive.The results showed that the Office of Industry and Trade of Indragiri Hilir Regency, Indragiri Hilir District Health Office, Tembilahan City Directorate General of Customs and Excise (DJBC), and Tembilahan City Port Area Police (KSKP) in the Supervision Synergy of Prohibition of Importing Used Clothing in Indragiri Regency Downstream Year 2016-2017 in supervising used Secondhand Clothing Imports has not been effective, this can be seen from the still discovery of markets selling used clothing in Tembilahan City, Indragiri Hilir Regency. In the case of cooperation the relevant agencies only carry out their respective duties and there is no good communication between the government parties as the Implementation of the Republic of Indonesia Minister of Trade Regulation Number 51 / M-Dag / Per / 7/2015 concerning Prohibition of Importing Used Clothing to the public and pedagogues used clothing and communication between Central and Regional agencies. Factors that inhibit the Synergy of Supervision of Central and Regional Agencies on Prohibition of Import of Used Clothing in Indragiri Hilir Regency 2016-2017, namely: Human Resources (HR), Limited facilities and infrastructure, Economic Factors, and Tembilahan Community Culture Culture.Keywords: Synergy, Supervision, Import, Used Clothing